Fabrication of functional edible packaging materials based on carboxymethyl cellulose and pomelo peel powder supplemented with Nisin as active compound - Andra-Gabriela Zorcă; Nicoleta Chira; Gabriela Olimpia Isopencu; Cristina Busuioc; Ovidiu-Cristian Oprea; Cristina-Ileana Covaliu-Mierlă; Alexandru Cîrîc; Gabriela Toader; Iuliana Mihaela Deleanu (Carbohydrate Polymer Technologies and Applications)
In this study, functional edible materials were prepared based on citric acid (CA) crosslinked carboxymethylcellulose (CMC), pomelo peel powder (PP), and Nisin. To benefit from agri-food waste that are available, two basic materials have been developed, both containing considerable amounts of PP. The formulations with a CMC:PP ratio of 1:2 (w/w) proved homogenous and compact, having suitable characteristics for edible packaging (EP): film thickness (below 0.2 mm), oxygen permeability (OP) (less than 1.3 meq.kg-1), reduced water solubility (approximately 40 %), good water vapor transmission rate (WVTR) (between 21.7 and 22.9 g.m2.h-1), and acceptable mechanical strength (3.4 MPa). Due to its complex composition, PP also contributes to antioxidant activity of films (approx. 130 µmol Trolox.g-1). A comparative analysis showed that increasing PP content (CMC:PP 1:4) has negative effects on morphological characteristics and on films’ properties because of pores formation and particle agglomeration. Nisin, used for its bio-preservation ability, had little effect on physico-chemical properties of films, being added in low concentration in all formulations. Due to Nisin and PP content the antibacterial activity of the composite packaging materials proved successful against B. subtilis, a Gram-positive bacterium and Escherichia coli, a Gram-negative bacterium.